2014
DOI: 10.1042/bst20130230
|View full text |Cite
|
Sign up to set email alerts
|

YODA signalling in the early Arabidopsis embryo

Abstract: During early embryogenesis, flowering plants establish their principal body plan starting with an apical-basal axis. An asymmetric division of the zygote gives rise to apical and basal cells with different developmental fates. Besides WOX (WUSCHEL-RELATED HOMEOBOX) transcription factors and the plant hormone auxin, the YDA (YODA)/MAPK (mitogen-activated protein kinase) pathway plays a major role in establishing different cell fates after the first zygotic division. In the present review, we summarize the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The yda mutants show a dwarf phenotype because the loss of function of the YDA gene affects zygote elongation and the normal development of the suspensor (the suspensor cells generally have morphology similar to the pro-embryos cells and the large vacuole characteristic of these cells is lacking). As a result, the apical-basal polarity of the future embryo is disrupted (Lukowitz et al 2004;Musielak and Bayer 2014). Conversely, YDA gain-of-function alleles promote exaggerated suspensor growth and suppress embryo development (Lukowitz et al 2004).…”
Section: Molecular View Of Abnormalities In Plant Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The yda mutants show a dwarf phenotype because the loss of function of the YDA gene affects zygote elongation and the normal development of the suspensor (the suspensor cells generally have morphology similar to the pro-embryos cells and the large vacuole characteristic of these cells is lacking). As a result, the apical-basal polarity of the future embryo is disrupted (Lukowitz et al 2004;Musielak and Bayer 2014). Conversely, YDA gain-of-function alleles promote exaggerated suspensor growth and suppress embryo development (Lukowitz et al 2004).…”
Section: Molecular View Of Abnormalities In Plant Embryogenesismentioning
confidence: 99%
“…The mpk3 mpk6 double mutants displayed the same phenotype of yda mutants (Musielak and Bayer 2014). It was identified in zygotic embryogenesis that the short suspensor (SSP) and grounded (GRD) genes also act by controlling the YDA-signaling pathway especially the SSP gene that is a member of the interleukin-1 receptor-associated kinase (IRAK)/Pelle-like kinase family of receptors likekinases (Wendrich and Weijers 2013).…”
Section: Molecular View Of Abnormalities In Plant Embryogenesismentioning
confidence: 99%
“…Over the past 2 decades, studies based primarily on the Arabidopsis model plant, have identified key molecules that include transcription factors, hormones, and micro-RNAs that mediate patterning of the embryo (reviewed in Lau et al, 2012;ten Hove et al, 2015;Jeong et al, 2016;Palovaara et al, 2016). In Arabidopsis, a MAP kinase cascade, mediated by YODA and two MAPKs, acts very early to regulate the first asymmetric cell division of the zygote (Lukowitz et al, 2004;Wang et al, 2007;Musielak and Bayer, 2014). Mutations in YODA and two MAPK genes inhibit elongation of the zygote and cause disruption of the asymmetric first cell division and suspensor cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that, in the zygote, SSP acts through the YDA MAPKKK and the MAPKs MPK3 and MPK6 (Wang et al 2007;Musielak and Bayer 2014). Therefore, one possible way in which WRKY2 and SSP could interact is that SSP/YDA-MAPK signaling targets the WRKY2 protein.…”
Section: Wrky2 Binds To Mpk3/6 and Is Activated By Phosphorylationmentioning
confidence: 99%